A wireless power transmission system with the multistate transmitting subsystem - Грецких, Д.В.; Лучанинов, А.И.; Гомозов, А.В. (Radiotekhnika, 2020)
Features of a wireless power transmission (WPT) systems with the transmitting subsystem based on a focused multistate radiators (MSR) systems are considered. The basic principles for constructing and managing such systems are described. Mathematical modeling of the field of the created focused MSR at the rectenna aperture is carried out. Based on the results obtained, a number of advantages of WPT systems built on the basis of MSR are distinguished in comparison with WPT systems built on the basis of single-position transmitting antennas. It is shown that from a practical point of view, the approach to the implementation of the transmitting subsystem of the WPT system based on the MSR is attractive, however, issues related to assessing the effectiveness of the large-aperture rectenna excited by a substantially non uniform field created by the MSR remain not clarified fully. An approach to the analysis of large-aperture rectennas excited by a substantially non uniform field was developed, the rectenna modeling was carried out based on this approach, the radiating structure of this rectenna consisted of a system of parallel microstrip conductors, Schottky rectifier diodes were included in their ruptures at regular intervals. The choice of such a design of the radiating structure made it possible to realize a two-layer microstrip rectenna converting electromagnetic fields with circular polarization into direct current. The receiving-rectifying elements transforming the field with vertical polarization were placed in the lower layer, and the receiving-rectifying elements transforming the field with horizontal polarization were placed in the upper layer. For a given rectenna excitation mode, an algorithm for constructing a DC power acquisition circuit was developed and its efficiency was evaluated.